Toxicological Evaluation of Tetrameles nudiflora Methanolic Extract - Sofna Dewita Sari Banjarnahor; Indah D Dewijanti; Marissa Angelina; Megawati Megawati; Sofa Fajriah (Journal of Tropical Life Science, 2015)
Exploration of Mekongga national park resulted in novel finding of anticancer property from Tetrameles nudiflora. The investigation of toxic features of T. nudiflora is vital for further studies of its pharmacological activities. Acute toxicity test was done on methanolic extracts of T. nudiflora in DDY mice. Animals were divided into 5 groups: Group 1 was given 1 ml solution of 2.5% Tween 80 in a single oral dose; Group 2, 3, 4 and 5 were orally administrated a single dose of 1, 2, 4 and 8 g/kg body weight T. nudiflora, respectively. Toxic effects of the extract were evaluated on the basis of behavioral observations in the form of locomotor activity; curiosity; defecation; urination and also animal mortality. Observations were carried out for 14 days. No significant changes on body weight, and behavioural activities were recorded. Mortality was recorded up to 22% of the male group, and 11% within the female group. The T.nudiflora extracts tested for toxicity against brine shrimp had 50% lethal concentration (LC50) values of 46.67 Î¼g/ml. It can be concluded that methanol extracts of T. nudiflora are potential to be explored as anticancer (LC50=46.67 Î¼g/ml). The extract is slightly toxic in male mice with Lethal Dose 50 (LD50) 12.6 g/kg body weight, and practically non toxic for female (LD50>15 g/kg body weight).Key words : Tetrameles nudiflora, brine shrimp lethality test, acute oral toxicity, LD 50.